The Influence of Reference Group on Consumers Decision to Purchase Big Bikes in Roi Et Province - Thechawattanapanicharoen, Thanakit; Ekkaphan, Mongkol (Journal of Roi Et Rajabhat University, 2021)
The purposes of this research were: 1) to study the reference group and the customers decision to purchase big bikes in Roi Et province. 2) to study the influence of reference group to the customers decision to purchase big bikes in Roi Et province. This research employed the quantitative research method. A questionnaire was used to collect data from the samples which consisted of 340 customers in Roi Et province. The data were analyzed by frequency, percentage, mean, standard deviation, multiple correlation analysis and multiple regression analysis. The results were as follows: 1) the influencing levels of the reference group and the customers decision for purchasing of big bikes were at the highest level. 2) the influences of informative and the normative had positive affect on customers decision for purchasing big bikes in Roi Et province. The influence of value-expressive had not statistical significance on the decision for purchasing of big bikes. Therefore, The results from this research can be used as a guideline to select an appropriate reference group to influence the customers decision to purchase big bikes and design an efficacy marketing plan.